Effectiveness of the application of Quantum Learning Model in terms of students' written mathematical communication skills - Dimiati Tari Utari; Dwi Priyo Utomo; Zukhrufurrohmah Zukhrufurrohmah (MEJ (Mathematics Education Journal), 2020)
AbstractThis research aimed (1) describe the implementation of learning in the classroom with the Quantum Learning model, (2) describe the students' written mathematical communication skills with Quantum Learning, and (3) describe the effectiveness of applying the Quantum Learning model to the written mathematics communication skills of junior high school students class VIII. The research was conducted in the even semester of the 2019/2020 school year in class VIII of SMP Muhammadiyah 2 Malang. This research is a type of descriptive research with quantitative methods. The initial stage of the research is the planning stage starting from determining the location and time of the study up to the validation of the research instruments used. The next stage is the implementation stage which is held three times by giving a description test to measure the ability of written mathematical communication at the third or final meeting. The last step is analyzing data obtained from the field. The data analysis technique used descriptive statistics. The results showed the average overall implementation of learning was in the good criteria of 83.92%. The ability of written mathematics communication in grade VIII A students of SMP Muhammadiyah 2 Malang is a very good criterion of 3.04. Therefore, it can be concluded that the application of the Quantum Learning model is effective to the written mathematics communication of junior high school students, especially in class VIII A.Keywords: Effectiveness, Quantum Learning, The implementation of learning, written mathematics communication.